Resolving epistemological issues in theoretical and methodological apparatus of institutional theories of organizations - Aksom, Herman; Chornyi, Anton (Technology audit and production reserves, 2018)
Agency-structure debate has become one of the central issues in modern organizational sociology and the most problematic theoretical area in institutional analysis. Since then researchers in new institutional sociology have focused on bringing agency and interests back in the theory that views rationality and motives as historically and culturally embedded and constructed by their institutional environments. To date, the most prospective theory is fashion perspective that sees interests and beliefs to be socially constructed and shaped by institutional forces. Accordingly, diffusion and adoption of administrative innovations is nothing but a result of these beliefs generated by institutional effects. Therefore the object of research is the essentiality of fashion management theory taking into account its ontological and epistemological characteristics. One of the most problematic areas is understanding the way institutions and fashions can be conceptualized upon the same mechanisms of emergence, reproduction and development. This paper attempts to clarify and resolve these two streams of literature by attending social construction perspective and revisiting its central tenets. Specifically, the present study put forward arguments that it is not homogeneity or symbolic pragmatic conformity should be the main units of analysis but the meanings that individuals attach to technical structures and elements; not the trajectories and waves of popularity of ideas and structures but the way subjective judgments and interpretations acquire objective status and eclipse former technical foundations. Based on logical generalization and morphological analysis, it is offered to reduce the conceptualization of institutions and organizations back from agency-centered depiction and strategic-perspective towards over-socialized picture with adequately addresses the prevalence of macro-level forces over micro-level individuals. It is concluded that neither former institutional theory nor its modern alternatives should focus exclusively on the trajectory and logic of diffusion of institutional templates.